Thermal Study in Solid State of Zn(II)-Diclofenac Complex: Behavior Kinetic of the Dehydration, Transition Phase and Thermal Decomposition - Kobelnik, Marcelo [UNESP]; Quarcioni, Valdecir Angelo; Ribeiro, Clovis Augusto [UNESP]; Vieira Capela, Jorge Manuel [UNESP]; Dias, Diogenes dos Santos [UNESP]; Crespi, Marisa Spirandeli [UNESP] (Chinese Chemical Soc, 2010)
The dehydration, thermal decomposition and transition phase stage of Zn(II)-diclofenac compound were studied by simultaneous TG-DTA and DSC techniques. The TG and DSC curves of this compound were obtained with the mass of sample of 2 and 5 mg. Additionally, DSC curves were carried out in opened and closed alpha-alumina pans under static and nitrogen atmosphere. The DTA and DSC curves show that this compound possesses exothermic transition phase between 170-180 degrees C, which it is irreversible (monotropic reaction) The kinetics study of this transition phase stage was evaluated by DSC under non-isothermal conditions. The obtained data were evaluated with the isoconversional method, where the values of activation energy (E(a) / kJ mol(-1)) was plotted in function of the conversion degree (alpha). The results show that due to mass sample, different activation energies were obtained From these curves a tendency can be seen where the plots maintain the same profile for closed lids and almost run parallel to each other.
Keywords: Zn(II)-diclofenac complex; Thermal behavior; Transition phase; Kinetic